Gender differences in adolescents’ academic achievement - Marcenaro-Gutiérrez, Óscar David; López-Agudo, Luis Alejandro; Ropero-García, Miguel Ángel (Sage, 2017)
Recent empirical literature has highlighted that adolescents show gender differences in academic performance. The present study intends to disentangle the contribution of some less well-known factors to that gender difference in the fourth year of secondary education. To this aim, we use recent methodological advances in decomposition techniques. We observe that girls are less likely to get low scores than boys. More interestingly, gender differences in the returns to expectations about the future have been found to explain most of this advantage for girls, while boys rely more on their initial learning skills to pass. Additionally, we found that boys are more prone to misbehaviour than girls, whereas boys’ academic results are more sensitive to changes in their family socio-economic status, which also explains a significant portion of the gender differences in academic achievement.
https://openpolicyfinder.jisc.ac.uk/id/publication/9574
Keywords: Rendimiento académico - Diferencias sexuales; Disciplina escolar; Gender differences in adolescence; Decomposition methods; Academic expectations; Misbehaviour; Students' actual performance